The Use of Visual Elements in the Opinion Comic Episode ‘Ramadan Full of Wisdom’ to Facilitate Readers: Penggunaan Elemen Visual Komik Opini Episode ”Ramadhan Penuh Hikmah” untuk Kemudahan Pembaca - Oely Maqwa Sharf; Miftachus Sifa; Haitsam Muhammad (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to examine how visual elements are used in opinion comics, as well as what visual elements are chosen by comic artists to convey messages effectively using the comedy genre while containing highly sensitive content. Through a qualitative-descriptive approach, data was collected from observation, interviews, and documentation. The results of the study indicate that to package highly sensitive content, a light-hearted approach is required. The technique applied in this Opinion Comic is to use the comedy genre as a medium for conveying messages, presented through simple yet representative visualisations. The religious theme raised was originally a very sensitive topic, but when packaged with visualisation appropriate to the comedy genre, it became entertainment that also educated readers of Opinion Comics and provided new insights from a different perspective. Highlights: Comedy as Medium – Humor softens sensitive topics for broader acceptance. Effective Visuals – Simple yet clear imagery enhances message delivery. Perspective Shift – Comics offer new insights through entertaining formats. Keywords: Visual Elements, Comedy Genre, Opinion Comics